Epidemiological analysis of lung and mediastinal neuroendocrine neoplasms in Japan based on the national database. (April 2022) - Matsuoka, Shunichiro; Koizumi, Tomonobu; Otsuki, Kengo; Tanaka, Yuriko; Kanda, Shintaro; Ide, Shogo; Mishima, Shuji; Takeda, Tetsu; Miura, Kentaro; Eguchi, Takashi; Hamanaka, Kazutoshi; Shimizu, Kimihiro
Abstract: Background: Neuroendocrine neoplasms (NENs) are rare and can originate from any body part. However, there are only few epidemiological studies, especially on lung and mediastinal NENs. This study investigated the epidemiological trends and differences between lung and mediastinal NENs in Japan. Methods: Patients with lung and mediastinal NENs were identified in a national hospital-based cancer registry between 2009 and 2015 in Japan. NENs were subclassified into neuroendocrine tumors (NETs) and neuroendocrine carcinomas (NECs). NECs were further subdivided into large neuroendocrine carcinomas (LCNECs) and small cell carcinomas (SCCs). We examined the patient characteristics: sex, age, histology, year of diagnosis, diagnostic opportunity, and initial treatment. Results: We identified 48, 433 patients with 47, 888 lung (98.9%) and 545 mediastinal (1.1%) NENs. The commonest subtype of lung NENs was SCCs (87%), followed by LCNECs (10%) and NETs (3%). In the mediastinum, SCCs were also the commonest (48%), followed by NETs (38%) and LCNECs (14%). The number of lung NEN annually increased; however, that of mediastinal NENs did not change over time. The mean age of patients with lung NETs was lower than that of patients with lung LCNECs and SCCs (NETs, 62 ± 14 years; LCNECs, 70 ± 9 years; SCCs, 71 ± 9 years; p < .001). The lung and mediastinal NENs were mainly detected based on symptoms, except for lung NETs. Surgical intervention, including multimodal therapy, was performed for 89.3% of lung NETs (surgery alone: 83.6%), while only 15.6% of lung NECs were treated with surgery. For the mediastinum, 75.9% of NETs were treated with surgery, with 27.1% of cases treated with surgery plus multimodal therapy. Surgery was performed more frequently for mediastinal NECs (37%) than for lung NECs (15.6%). Conclusions: This study highlights differences in trends of lung and mediastinal NENs. This study's findings support the importance of epidemiological evaluations based on the primary sites and histological subtypes. Highlights: The most frequent subtype of lung and mediastinal NENs was small cell carcinomas. A continuous increase was observed in the number of lung NENs, but that of mediastinal NENs did not significantly change. Lung and mediastinal NENs were mainly detected based on symptoms except for lung NETs. Surgical intervention was performed more frequently for mediastinal NECs than lung (lung: 15.6%, mediastinum: 37%).